In Arid Zone… Exploring horticulture-based integrated farming for more return - Singh, Akath; Tanwar, SPS; Meghwal, PR; Kumar, Prdeep; Kumar, Praveen (Indian Horticulture, 2019)
Introduction of ber varieties, viz. Gola and Seb, has made it then as commercial crop. Arid climate suits for finest quality of pomegranate. Datepalm cultivation is also being promoted on large scale in arid regions. With improved marketing and processing facilities, some of the horticultural crops have now emerged as profitable ventures, viz. aonla, bael, phalsa, fig, kair, gonda/lasora, karonda, pilu etc. The region suits best for vegetable crops like mateera, snap melon, kachari, musk melon, round melon, bean, khejri, cowpea, sangri (khejri pods), Indian, sword bean, cow pea, drum stick etc; medicinal and aromatic plants like aloe vera, guggul, satawar, aswagandha, isabgol, mehndi etc; spices like cumin, methi, fennel, dill etc. Dehydrated vegetables are an important delicacy for marwadi community globally.